2000
DOI: 10.1074/jbc.275.15.10937
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Metabolism of Isoleucine to Active Amyl Alcohol in Saccharomyces cerevisiae

Abstract: The metabolism of isoleucine to active amyl alcohol (2-methylbutanol) in yeast was examined by the use of 13 C nuclear magnetic resonance spectroscopy, combined gas chromatography-mass spectrometry, and a variety of mutants. From the identified metabolites a number of routes between isoleucine and active amyl alcohol seemed possible. All involved the initial decarboxylation of isoleucine to ␣-keto-␤-methylvalerate. The first, via branched chain ␣-ketoacid dehydrogenase to ␣-methylbutyryl-CoA, was eliminated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 20 publications
6
125
0
Order By: Relevance
“…The catabolism of amino acids has been well documented in bacteria and yeasts (18,(142)(143)(144). In fruits, it has been demonstrated that the reactions for the derivation of volatile compounds from branched amino acids follow the pathway found in some of these microorganisms.…”
Section: Mcintoshmentioning
confidence: 99%
See 3 more Smart Citations
“…The catabolism of amino acids has been well documented in bacteria and yeasts (18,(142)(143)(144). In fruits, it has been demonstrated that the reactions for the derivation of volatile compounds from branched amino acids follow the pathway found in some of these microorganisms.…”
Section: Mcintoshmentioning
confidence: 99%
“…These aldehydes can be reduced to their corresponding branched alcohol (2-methyl-butanol, 3-methyl-butanol and 2-methyl-propanol) by action of the ADH enzyme, which uses NAD(P) + as a cofactor (30,140,143,145,147). The transformation of amino acids into alcohols is known as the Ehrlich pathway, in which the key enzymes are transaminases, decarboxylases and dehydrogenases (148).…”
Section: Mcintoshmentioning
confidence: 99%
See 2 more Smart Citations
“…K-Ketoisovalerate and K-keto-L-methylvalerate show similar patterns towards NaCl and pH as K-ketoisocaproate. Cross talk between catabolic and anabolic reactions of the branched-chain amino acid metabolism may explain the formation of the di¡erent keto acids and fusel alcohols, as described by Dickinson et al [6,7]. Van der Sluis [16] has not reported the accumulation of these K-keto acids, which are not derived from leucine.…”
Section: Substrate Consumption and Formation Of Extracellularmentioning
confidence: 99%